Peningkatan Kualitas Pelayanan UPK Perkampungan Budaya Betawi Setu Babakan - Rizki Nurul Nugraha; Putri Indriani (Peneliti.net, 2022)
Betawi Cultural Village is one of the cultural and tourist preservation areas in DKI Jakarta. Betawi Village is also currently one of the destinations that are in demand by local tourists for education and entertainment. The purpose of this study is to determine the quality of services in the current Betawi Cultural Village and whether there are improvements made by the managers of the Betawi Cultural Village to maintain the existence in the preservation of Betawi culture. This research uses a qualitative method by using interview techniques to managers in collecting data. The results that the author gets from this study are that managers and service industry players show that Betawi Cultural Village has improved its services by continuing to evaluate and what visitors need in the following year.